Aspek Manajemen Dan Kepatuhan Prinsip Syariah Dalam Penilaian Kesehatan BMT Usaha Gabungan Terpadu (UGT) Sidogiri Pasuruan - Rahajeng, Yekti (Fakultas Ekonomi dan Bisnis Universitas Panca Marga, 2024)
This research to know the health level of BMT UGT Sidogiri in terms of management and compliance with sharia principles. The research method used in this research was carried out statistic descriptive. The results of this research say that the implementation of management and compliance with sharia principles at BMT UGT Sidogiri in 2023 is good and compliant. Especially in capital management, there are still weaknesses but they are still in safe condition. The weakness lies in the growth rate of own capital is smaller than the growth rate of assets and the growth rate of own capital derived from members is less than 10% compared to the previous year. Even so, BMT UGT Sidogiri in 2023 has implemented Good Corporate Governance and includes financial institutions that comply with sharia principles. Keyword: Baitul Maal wat Tamwil, health assessment, management, Sharia compliance